Fabrication of circular polarized luminescent helical fibers from chiral phenanthro[9, 10]imidazole derivatives. (11th November 2016) - Li, Bing Shi; Wen, Rongsen; Xue, Shan; Shi, Lin; Tang, Zhiyong; Wang, Zhiming; Tang, Ben Zhong
Abstract : Violet fluorescent helical nanofibers with circular polarized luminescence fabricated by the self-assembly of chiral phenanthro[9, 10- d ]imidazole (PIM) derivatives. Abstract : This work provides a simple but efficient way of constructing violet fluorescent helical nanofibers by the self-assembly of chiral π–π conjugated molecules, phenanthro[9, 10- d ]imidazole (PIM) derivatives. PIM derivatives are well-known functional molecules, but the construction of PIM into functional architectures has not been carried out to date. By introducingl - andd -aniline pendants into PIM derivatives, PIM-d -Ala and PIM-l -Ala are synthesized, which not only have the properties of aggregation induced circular dichroism (AICD) and circular polarized luminescence (CPL), but also have the capacity to self-assemble into helical fibers. They have important applications in the increasing demand for the miniatured optics and electronic devices.